In Situ Generated Colloid Transport of Cu and Zn in Reclaimed Mine Soil Profiles Associated with Biosolids Application - Jarrod O. Miller; Anastasios D. Karathanasis; Christopher J. Matocha (Applied and Environmental Soil Science)
Areas reclaimed for agricultural uses following coal mining often receive biosolids applications to increase organic matter and fertility. Transport of heavy metals within these soils may be enhanced by the additional presence of biosolids colloids. Intact monoliths from reclaimed and undisturbed soils in Virginia and Kentucky were leached to observe Cu and Zn mobility with and without biosolids application. Transport of Cu and Zn was observed in both solution and colloid associated phases in reclaimed and undisturbed forest soils, where the presence of unweathered spoil material and biosolids amendments contributed to higher metal release in solution fractions. Up to 81% of mobile Cu was associated with the colloid fraction, particularly when gibbsite was present, while only up to 18% of mobile Zn was associated with the colloid fraction. The colloid bound Cu was exchangeable by ammonium acetate, suggesting that it will release into groundwater resources.